The role of the family’s social and economic level on the academic achievement: A field study with a sample of intermediate third-year student - Parzheen Sadic Marouf (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The aim of the current research is to determine the role of the family’s social and economic level on the academic achievement of students in the third intermediate grade for the academic year 2022-2023. The research relied on a social survey approach. The research sample was randomly selected and consisted of 300 male and female students distributed among eight government schools in the city of Erbil. Data was collected about the social and economic level of the students’ families using a questionnaire form that was filled out by the students of the research sample. The data was analyzed by applying the Pearson equation, percentages, and phi using the statistical program for social sciences, IBM Spss23. The results of the research showed that there is a correlation between the economic level of the family, represented by (the parents’ occupation, housing status, family income, children’s employment, the provision of separate rooms, school supplies, and the costs of private lessons, in addition to the role of some other economic factors) on the children’s academic achievement, One of the most important recommendations of the research is to open strengthening courses for students in the basic curricula during the summer vacation by the Ministry of Education and also educate parents of students about the need to pay attention to their children’s academic achievement.